Hubungan Kompetensi Guru Profesioal dan Dukungan Orang tua dengan Motivasi Belajar Siswa SMP Negeri 13 Kolaka Utara - Marfuatul Jannah Bakhtiar; Kamaruddin Hasan; Muhammad Ardiansyah (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Abstract: Students’ learning motivation is a crucial factor in determining the success of the learning process. Learning motivation is influenced by various external factors, particularly teachers’ professional competence and parental support. This study aims to examine the relationship between teachers’ professional competence and students’ learning motivation, the relationship between parental support and students’ learning motivation, and the simultaneous relationship between teachers’ professional competence and parental support and students’ learning motivation at SMP Negeri 13 Kolaka Utara. This study employed a quantitative approach with a correlational research design. The research sample consisted of 119 students selected using proportional sampling techniques. Data were collected through Likert-scale questionnaires measuring teachers’ professional competence, parental support, and students’ learning motivation. The data were analyzed using Pearson correlation analysis and multiple regression analysis at a significance level of 0.05. The results indicate that teachers’ professional competence has a positive and significant relationship with students’ learning motivation. Parental support also shows a positive and significant relationship with students’ learning motivation. Furthermore, teachers’ professional competence and parental support simultaneously have a significant relationship with students’ learning motivation, although the strength of the relationship is relatively low. These findings highlight the importance of collaboration between teachers and parents in fostering students’ learning motivation. Strengthening teachers’ professional competence and enhancing parental involvement are expected to contribute positively to improving students’ motivation to learn. Keywords: teachers professional competence; parental support; students learning motivation. Abstrak: Motivasi belajar siswa merupakan faktor krusial dalam menentukan keberhasilan proses pembelajaran. Motivasi belajar dipengaruhi oleh berbagai faktor eksternal, khususnya kompetensi profesional guru dan dukungan orang tua. Penelitian ini bertujuan untuk mengkaji hubungan antara kompetensi profesional guru dengan motivasi belajar siswa, hubungan antara dukungan orang tua dengan motivasi belajar siswa, serta hubungan simultan antara kompetensi profesional guru dan dukungan orang tua dengan motivasi belajar siswa di SMP Negeri 13 Kolaka Utara. Penelitian ini menggunakan pendekatan kuantitatif dengan desain penelitian korelasional. Sampel penelitian terdiri atas 119 siswa yang dipilih menggunakan teknik sampling proporsional. Data dikumpulkan melalui angket skala Likert yang mengukur kompetensi profesional guru, dukungan orang tua, dan motivasi belajar siswa. Data dianalisis menggunakan analisis korelasi Pearson dan analisis regresi ganda pada taraf signifikansi 0,05. Hasil penelitian menunjukkan bahwa kompetensi profesional guru memiliki hubungan positif dan signifikan dengan motivasi belajar siswa. Dukungan orang tua juga menunjukkan hubungan positif dan signifikan dengan motivasi belajar siswa. Selain itu, kompetensi profesional guru dan dukungan orang tua secara simultan memiliki hubungan yang signifikan dengan motivasi belajar siswa, meskipun kekuatan hubungannya tergolong rendah. Temuan ini menegaskan pentingnya kolaborasi antara guru dan orang tua dalam menumbuhkan motivasi belajar siswa. Penguatan kompetensi profesional guru serta peningkatan keterlibatan orang tua diharapkan dapat memberikan kontribusi positif dalam meningkatkan motivasi belajar siswa. Kata kunci: kompetensi guru profesional, dukungan orang tua, motivasi belajar siswa.